Pengaruh Celebrity Endorser, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Produk Sunscreen Azarine di Yogyakarta - Romlah, Romlah; Sudarusman, Eka (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This study aimed to analyse the effect of celebrity endorsers, product quality, and price on purchasing decisions for Azarine sunscreen products in Yogyakarta. This research is quantitative research, the sample in this study were consumers who live in Yogyakarta and have purchased Azarine sunscreen with respondents aged 17 years and over. With purposive sampling technique, the sample in this study amounted to 120. The analysis method used in this research is multiple linear analysis. The results of this study indicate that (1) celebrity endorsers have a positive and significant effect on purchasing decisions, (2) product quality has an insignificant effect on purchasing decisions, (3) price has a positive and significant effect on purchasing decisions.